The Influence of Cooperative Learning Model Type Group Investigation Toward Results of Learning Science Materials of Students - Heny Ekawati Haryono (Universitas Lambung Mangkurat, 2020)
Student learning outcomes are still low due to the use of learning models that are less varied. Therefore, researchers apply the cooperative learning model type group investigation in learning science. This study aims to describe the influence of the cooperative learning model type group investigation on the learning outcomes of science materials in the fifth grade students of SDN 1 Banjarejo. This type of research used is quasi-experimental design with nonequivalent control group design. The sample of this research is the VB class SDN 1 Banjarejo experimental class and class V SDN 1 Banjarejo as the control class. Data collection techniques for learning outcomes use multiple choice tests and descriptions. Learning outcomes data were analyzed by independent t-test and gain test. The results of the analysis of the pretest data showed that there was no difference in the average pretest score between the two samples. The results of posttest data analysis showed that there were differences in the average posttest scores of the experimental and control classes, with the difference in the average experimental class being higher at 5.50. Large increase in the average normalized gain in the experimental class by 0.41 (medium), while in the control class by 0.29 (low). These results provide the conclusion that the cooperative learning model type group investigation has a significant and positive influence on science learning outcomes in elementary students.